Evaluation of Hafıza-i Saltanat theater play and activities in terms of history teaching - Muhammet Ahmet Tokdemir; Gülin Karabağ; Cemile Açıl (Turkish History Education Journal)
The aim of this study is to evaluate the Hafıza-i Saltanat theatre play and activities, which combines evidence-based learning and history-themed theatre, written based on archival documents, in terms of history teaching. In this study, firstly, Hafıza-i Saltanat theatre play and its activities were introduced. Then, the play was examined in the context of historical reality, 10th grade history course curriculum achievements and textbooks, and the activities of the play were examined with student opinions in the context of age, level, knowledge, skills and 10th grade history course curriculum achievements. Document analysis and holistic single case study design, which are qualitative research methods, were used in the study. While the text of the theatre play, video recording and activities were evaluated through document analysis, watching the play and implementing the activities were handled as a holistic single case. The study group consisted of a total of 19 volunteer students, 6 boys and 13 girls, studying at the 10th grade level of secondary education. The data collection tools of the study were the text of the Hafıza-i Saltanat theatre play, the video recording of the play, the activities of the play, the video recordings of the application and the researcher's observation notes. The data obtained from the data collection tools were analyzed by descriptive analysis method. As a result of the study, it was determined that the archival documents used in the play were taken from the Mühimme Books, where the records of the Divan-ı Hümayun were kept, and the issues that were not included in the documents were included in the fiction by considering the historical facts, and for this reason, the play was written and performed largely in parallel with the historical reality. At the same time, it has been determined that the play and its activities meet and gain the achievements of units 4, 5, 6 and 7 of the 10th Grade History Course Teaching Program. It has been concluded that the use of Hafıza-i Sultanate play and activities in history lessons is appropriate for the specified achievements and that it supports the evidence-based learning approach and provides students with the necessary knowledge and skills.